INOVASI PEMBELAJARAN BERUPA MATERI DAN GAME EDUKATIF MELALUI PEMANFAATAN AI DI SD NEGERI 6 METRO BARAT - Hartina, Siti; Faradita, Meirza Nanda; Afiani, Kunti Dian Ayu (Universitas Trunojoyo Madura, 2025)
This study aims to analyse the scientific literacy skills of elementary school students in learning Natural and Social Sciences (IPAS) with a focus on four indicators, which are understanding basic scientific concepts (content knowledge), critical thinking and inquiry skills (scientific inquiry), the ability to apply scientific concepts in a social context (contextual application), and scientific attitudes. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Observations were conducted to observe learning activities, while interviews were conducted with teachers and principals to find out their responses regarding students' scientific literacy. The results of the study indicate that students' understanding of basic scientific concepts is quite good, especially when learning uses a practical approach and is based on the context of everyday life. Students' critical thinking and inquiry skills still need to be improved, especially in terms of asking questions and formulating hypotheses. Students' ability to apply scientific concepts to a social context shows positive results, especially through project activities that are relevant to the surrounding environment. Students' scientific attitudes, such as curiosity, are starting to develop, but attitudes of accuracy and precision still require further development. The conclusion of this study is that elementary school students' scientific literacy can be improved through inquiry-based learning methods, projects, and experiments involving real-life contexts and active guidance from teachers. This study recommends strengthening learning programs that encourage critical thinking, scientific attitudes, and the application of science in everyday life.